Pembuatan Nomor Induk Berusaha (NIB) Sebagai Dasar Legalitas Usaha Pada UMKM di Kelurahan Sentul - Putri Kurniawati; Nabil Abiyu Rohman; Adistia Nurul Aini; Vivia Nur Salsabila Trisnalia; Ardi Zulva Budianto; Aji Qolbu Wibawa Syah’alam; Dewi Puspa Arum (Universitas Muhammadiyah Manado, 2023)
Business legality plays a very important role in running a business, because the legality of a business is a form of licensing from the implementation of business activities provided by the authorized party to the business owner. The legality also acts as a benchmark that the business established can be said to be feasible, legal and ongoing. The problem that is often encountered in the surrounding community, especially Micro, Small and Medium Enterprises (MSMEs), is that understanding the importance of having legality and how to make legality for their business causes them not to have business legality. Therefore, this service activity aims to provide understanding to the community in the form of socialization of what business legality is and provide assistance in terms of making business legality, especially for business actors in the Sentul village area. The method carried out in this assistance activity is divided into three stages, in the first stage the group 28 KKN-T UPN